Estimation of replenishable groundwater resource for sustainable development: A case study for Ghumuda watershed of Odisha - PARAMAGURU, P. K.; PAUL, J. C.; PANIGRAHI, B. (Journal of Soil and Water Conservation, 2020)
For proper management, utilization and development of valuable natural resource like groundwater which is rapidly declining day by day, a proper and reliable quantification is indispensable. In this context, the present study attempts to assess the draft and dynamic groundwater resource of Ghumuda watershed of Sundergarh block in Sundergarh district, Odisha. For systematic and logical assessment, the groundwater resource of the study area was evaluated based on Groundwater Estimation Committee (GEC) norms. The study estimates the net annual availability of groundwater to be 80.989 ha-m while the annual draft is estimated to be 10.18 ha-m. The total groundwater recharge from different sources was also computed using norms of GEC-1997. The present study also reveals that the stage of groundwater development in the study area is very low (12.57%) which falls in safe category. So there is a tremendous scope for further exploitation of groundwater resource in the selected watershed.